Sialolipoma of the parotid gland diagnosis and conservative surgical approach: A case report. Issue 3 (May 2016) - Tomo, Saygo; Pereira, Rafael Marques; Queiroz, Sâmia Alves de; Careno, Leandro Barbuio; Stefanini, Aline Reis; Simonato, Luciana Estevam
Abstract: Salivary glands demonstrate a high variability of benign neoplastic processes. Among them, fat tissue containing tumors might be found, which are rare and might be classified according to the histopathologic characteristics and biological behavior. Sialolipoma is a biphasic benign neoplasm of salivary glands characterized by the proliferation of mature fat tissue associated to interspersed salivary gland components. Sialolipoma might only be diagnosed by histopathologic analysis. This paper describes a rare case of left parotid gland sialolipoma in an adult male patient without any systemic pathology reported. The lesion was submitted to Computed Tomography (CT) Fine Needle Aspiration (FNA) which revealed the fat containing of the lesion and also its benign behavior. Treatment approach was the conservative surgical excision by partial parotidectomy in field hospital under general anesthesia, resulting in the removal of a massive tumor yellow in color and fibrous in consistence. After excision, the lesion underwent histopathologic analysis which confirmed the diagnosis of sialolipoma.